THE CONTENT AND ESSENCE OF THE FORMATION OF INFORMATION CULTURE IN STUDENTS ON THE EXAMPLE OF FOREIGN EXPERIENCES (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Information culture is an integral part of the educational process today. The rapid development of digital technologies, the wide spread of the Internet and the easy availability of information make it necessary to form an information culture in students. Information culture includes not only the ability to correctly receive and use information, but also the ability to analyze, evaluate and effectively present it. This article examines the content and nature of information culture, as well as the process of formation of information culture in students on the example of foreign experiences.